1966
DOI: 10.1071/bi9660619
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Coumaphos in Larvae of the Cattle Tick Boophilus Microplus

Abstract: Summwry[82P]Coumaphos, a phosphorothionate, was rapidly absorbed and metabolized by cattle tick larvae dipped in aqueous suspensions of the acaricide. One metabolite was shown by chromatographic, spectroscopic, and cholinesterase inhibition evidence to be the oxygen analogue, a more potent in vitro cholinesterase inhibitor than the parent compound. Other water-soluble~ metabolites were only tentatively identified. Sublethal doses were metabolized mainly to water-soluble materials and a small quantity of oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1969
1969
1985
1985

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…These results suggested that the resistance mechanism in the Mackay strain differed from that in the Ridgelands and Biarra strains. When ticks are treated with coumaphos some of the chemical is metabolized into the oxygen analogue or phosphate (coroxon), a much more potent inhibitor of acetylcholinesterase than the parent compound (Roulston, Schuntner, and Schnitzerling 1966). Thus, the toxic action of coumaphos largely depends on the amount of coroxon present.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that the resistance mechanism in the Mackay strain differed from that in the Ridgelands and Biarra strains. When ticks are treated with coumaphos some of the chemical is metabolized into the oxygen analogue or phosphate (coroxon), a much more potent inhibitor of acetylcholinesterase than the parent compound (Roulston, Schuntner, and Schnitzerling 1966). Thus, the toxic action of coumaphos largely depends on the amount of coroxon present.…”
Section: Resultsmentioning
confidence: 99%
“…1971) of the method of Stone and Haydock (1962) was used in which larvae were confined in filter paper packets impregnated with olive oil containing the acaricides. In the latter technique larvae were dipped in aqueous suspensions of the acaricides as described by Roulston et al (1966). After dipping, the wet masses of larvae were partially dried on cotton wool balls.…”
Section: Acaricidal Treatment Of Larvaementioning
confidence: 99%
“…External and internal radioactive compounds were extracted by methods previously described (Roulston et al 1966), the former being determined by counting in a Packard Tri-Carb liquid scintillation spectrometer. The rate of penetration conformed very closely to first-order reaction kinetics and was expressed as a half-life value (to.5) which is the time for half of the initial external deposit to penetrate.…”
Section: Penetration and Metabolismmentioning
confidence: 99%
“…B Bromine oxidation of thio parent (Roulston et al 1966). C pH 11 bis-deethylation of parent (Stenersen 1969).…”
Section: Non-radioactive Reference Compoundsmentioning
confidence: 99%
“…Larvae were dosed with labelled or unlabelled chemicals by immersion in aqueous suspensions of chemical for 5 min (Roulston et al 1966). Duplicate samples weighing 0·2 g were used for metabolism studies and for the determination of AChE, while duplicate samples of c. 100 larvae were subsampled, after dosage, into paper packets and incubated for 24 h at 30°C and 90 % R.H. to determine mortality.…”
Section: Dosage Of Larvaementioning
confidence: 99%